واقع وتحديات التمويل المصغر في الجزائر - الوكالة الوطنية لتسيير القرض المصغر نموذجا- - زهواني, عبد الرزاق; حاقة, الازهاري; شبرو, نذير (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى تبيان دور التمويل و بالأخص التمويل المصغر في الجزائر، وأهميته في دعم المشاريع وإنشاء المؤسسات المصغرة ( الإنتاجية، خدماتية ...الخ) وكذلك التطرق إلى آليات و هيئات الدعم التي انشائتها الدولة لمثل هذه المشاريع، ولقد إعتمدنا في ذلك على المنهج الوصفي التحليلي للإحاطة بمختلف مواضيع الدراسة، وخلص البحث إلى أن آليات و هيئات الدعم التي أنشأتها الدولة لتمويل المشاريع المصغرة في الجزائر لها دور مهم و كبير في خلق الكثير من المؤسسات والمشاريع الصغيرة وخاصة في الأرياف، و بالتالي امتصاص المزيد من البطالة ودعم الإنتاج الوطني من جراء هاته المشاريع المصغرة. This study aims to clarify the role of finance, especially microfinance, in Algeria, and its importance in supporting projects and establishing small enterprises (productivity, services, etc.), as well as addressing the support mechanisms and bodies established by the state for such projects. and we have relied on this approach. Analytical descriptive to cover the various topics of the study, and the research concluded that the support mechanisms and bodies established by the state to finance micro-projects in Algeria have an important and significant role in creating many small enterprises and projects, especially in the countryside, thus absorbing more unemployment and supporting national production as a result of These are the mini projects.
The reality and challenges of microfinance in Algeria National Agency for Microcredit Management as a model
مقال
Keywords: التمويل- التمويل المصغر- الجزائر- آليات الدعم- المشاريع المصغرة